2023
DOI: 10.3390/en16248058
|View full text |Cite
|
Sign up to set email alerts
|

Study on Flow and Heat Transfer Characteristics in Lamilloy Structure with Different Configurations of Internal Minichannels

Tao Yang,
Xiaoming Zhang,
Zhenyuan Chang
et al.

Abstract: This paper proposes a novel lamilloy cooling structure equipped with internal minichannels used in a combustor flame cylinder. The overall flow and heat transfer characteristics of three different internal minichannel configurations (parallel-flow, counter-flow, and staggered arrangements. PF, CF, and SF for short) are analyzed and compared. From the analysis of the heat transfer characteristic, it is found that the CF structure possesses the best cooling effect and temperature uniformity. The average cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Singh et al [26] has pointed out that the RNG k − ε model has the best accuracy for simulating zigzag MCHS. In addition, according to our study of similar structures, we have found that the RNG k − ε model is more suitable for the prediction of lamilloy cooling with internal channels [44,45]. Therefore, in this work, the RNG k − ε model was utilized using the commercial program ANSYS CFX 17.0.…”
Section: Brief Description Of Cfd Modelingmentioning
confidence: 99%
“…Singh et al [26] has pointed out that the RNG k − ε model has the best accuracy for simulating zigzag MCHS. In addition, according to our study of similar structures, we have found that the RNG k − ε model is more suitable for the prediction of lamilloy cooling with internal channels [44,45]. Therefore, in this work, the RNG k − ε model was utilized using the commercial program ANSYS CFX 17.0.…”
Section: Brief Description Of Cfd Modelingmentioning
confidence: 99%